Content Analysis Made Simple for Students. An Interactive Online Application Solution - Briciu, Victor-Alexandru; Briciu, Arabela; Nechita, Florin (Cognitive Science – New Media – Education, 2019)
This paper aims to present an interactive online solution developed for students to better understand the application of content analysis (as a research method) and the use of a coding scheme (as the research instrument) by using a software platform, an application for analysing an online place brand’s content, in terms of the characteristics of a place brand’s identity communicated through official websites.